2018
DOI: 10.1002/tafs.10020
|View full text |Cite
|
Sign up to set email alerts
|

Egg Viability and Egg‐to‐Fry Survival of Captive‐Reared Chinook Salmon Released to Spawn Naturally

Abstract: Conservation hatchery strategies for anadromous salmonids are designed to boost depressed wild populations while conserving genetic resources. Captive rearing is an approach in which eggs or juveniles are collected from wild fish, taken into a hatchery and reared to maturation, and then released to spawn. In this study, we quantified spawn timing and redd production for captive‐reared and wild Chinook Salmon Oncorhynchus tshawytscha and measured survival of eggs to the eyed stage of development (egg viability)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…; Stark et al. ). Juvenile fitness‐related traits such as size and emergence timing have also been linked to maternal phenotype (Braun et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Stark et al. ). Juvenile fitness‐related traits such as size and emergence timing have also been linked to maternal phenotype (Braun et al.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have indicated differential reproductive success between hatchery and natural conspecifics (Fleming and Gross 1993;Fleming and Petersson 2001;Williamson et al 2010;Anderson et al 2012;Ford et al 2012;Kozfkay et al 2017) and have related this difference to age at maturation, fish size and competition, timing of spawning, redd construction and location, or egg viability (Williamson et al 2010;Anderson et al 2012;Ford et al 2012;Stark et al 2018). Juvenile fitness-related traits such as size and emergence timing have also been linked to maternal phenotype (Braun et al 2013).…”
Section: Reintroduction Of Sockeye Salmon Into Redfish Lakementioning
confidence: 99%
“…For example, Gallinat and Chang (2013) found significantly lower reproductive potential in captive brood and supplementation-reared females compared with natural-origin females of the same stock, with fecundity decreasing as time spent in the hatchery environment increased. Stark et al (2018) also found significantly lower egg viability and egg-to-fry survival from captivereared salmonids compared with natural-origin salmonids spawning in the East Fork Salmon River. Many of the biological changes that can occur as the result of captivity are unknown (Horreo et al 2017), but reducing the number of generations in captivity is expected to reduce the extent or degree of domestication selection (Frankham 2008;Horreo et al 2017).…”
mentioning
confidence: 83%
“…Stark et al. (2018) also found significantly lower egg viability and egg‐to‐fry survival from captive‐reared salmonids compared with natural‐origin salmonids spawning in the East Fork Salmon River. Many of the biological changes that can occur as the result of captivity are unknown (Horreo et al.…”
mentioning
confidence: 96%
“…; Stark et al. ). Laboratory studies have shown that intrinsic factors can greatly influence early‐life survival in salmonids either independently or through an interaction with extrinsic factors (Heath et al.…”
mentioning
confidence: 97%